A novel tissue engineering technique for regeneration of lost interdental papillary height - Rutuj Surana; Vaishali Ashtaputre; Satish Doiphode; Kiran Kharat; Purshottam Rakhewar; Maya Mhaske (Wolters Kluwer Medknow Publications, 2010)
Open interdental spaces caused by papillary gingival recession are one of the most common problems faced in dentistry. Surgical and nonsurgical periodontal treatments for regeneration of lost papillary height have been reported with limited success. The present study reports effectiveness of autologous cultured fibroblast injections, a tissue engineering technique for papillary regeneration. A black triangle caused by Tarnow's and Nordland's class I papillary gingival loss was reported in maxillary anterior region of a young male patient. An autologous gingival biopsy was cultured in a biotechnology lab for the growth and expansion of fibroblasts. Cultured fibroblast suspension was injected into the receded papilla twice at an interval of 5 days. Follow-ups were recorded on the 6th day, 15 th day, at 1 month and at 2 months. Complete fill of black triangle was noted at the end of 2 months. No inflammatory or immune reactions were noted at the site of injection. Autologous cultured fibroblast injections are safe, efficacious, and an acceptable treatment option for the regeneration of lost papillary height.